Human Resource-Oriented Strategic Management to Improve Organizational Competitiveness - Muhamad Agung Dharmajaya (SEAN Institute, 2025)
Increasingly complex organizational competition demands the implementation of management strategies that focus not only on operational aspects but also on strategic human resource (HR) management. HR is a crucial asset that determines organizational performance and competitiveness. This study aims to analyze the application of HR-based strategic management in enhancing organizational competitiveness, with a focus on recruitment and selection practices, training and development, performance management, compensation and rewards, employee welfare, innovation, and work flexibility. This study used a qualitative approach with descriptive methods. Data were obtained through in-depth interviews with key informants, observations of organizational activities, and documentation studies related to HR policies. Data analysis was conducted using descriptive qualitative methods through the stages of data reduction, data presentation, and conclusion drawing, using source triangulation to enhance data validity. The results indicate that effective HR-oriented strategic management, including strategic alignment, skills development, performance management, fair compensation and reward systems, and attention to employee welfare, can increase employee motivation, engagement, and productivity. A work environment that supports innovation, flexibility, and continuous learning also plays a crucial role in strengthening organizational competitiveness.